Explore Westonci.ca, the premier Q&A site that helps you find precise answers to your questions, no matter the topic. Explore a wealth of knowledge from professionals across various disciplines on our comprehensive Q&A platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
Certainly! Let's go through the steps to prove that [tex]\(\cos 2\theta = \sin 4\phi\)[/tex] given [tex]\(\tan \theta = \frac{1}{7}\)[/tex] and [tex]\(\tan \phi = \frac{1}{3}\)[/tex].
### Step-by-Step Solution:
1. Represent [tex]\(\theta\)[/tex] and [tex]\(\phi\)[/tex] using arctangent:
Since [tex]\(\tan \theta = \frac{1}{7}\)[/tex], we have:
[tex]\[ \theta = \tan^{-1}\left(\frac{1}{7}\right) \][/tex]
Similarly, since [tex]\(\tan \phi = \frac{1}{3}\)[/tex], we have:
[tex]\[ \phi = \tan^{-1}\left(\frac{1}{3}\right) \][/tex]
2. Double-angle formula for cosine:
For [tex]\(\cos 2\theta\)[/tex], we use the double-angle identity for cosine in terms of tangent:
[tex]\[ \cos 2\theta = \frac{1 - \tan^2 \theta}{1 + \tan^2 \theta} \][/tex]
Substituting [tex]\(\tan \theta = \frac{1}{7}\)[/tex]:
[tex]\[ \cos 2\theta = \frac{1 - \left(\frac{1}{7}\right)^2}{1 + \left(\frac{1}{7}\right)^2} = \frac{1 - \frac{1}{49}}{1 + \frac{1}{49}} = \frac{\frac{48}{49}}{\frac{50}{49}} = \frac{48}{50} = \frac{24}{25} \][/tex]
Thus,
[tex]\[ \cos 2\theta = 0.96 \][/tex]
3. Double-angle formula for sine:
To find [tex]\(\sin 4\phi\)[/tex], use the identity:
[tex]\[ \sin 4\phi = 2 \sin 2\phi \cos 2\phi \][/tex]
First, find [tex]\(\sin 2\phi\)[/tex] and [tex]\(\cos 2\phi\)[/tex] using the double-angle formulas for sine and cosine:
[tex]\[ \sin 2\phi = \frac{2 \tan \phi}{1 + \tan^2 \phi} \][/tex]
Substituting [tex]\(\tan \phi = \frac{1}{3}\)[/tex]:
[tex]\[ \sin 2\phi = \frac{2 \left(\frac{1}{3}\right)}{1 + \left(\frac{1}{3}\right)^2} = \frac{\frac{2}{3}}{1 + \frac{1}{9}} = \frac{\frac{2}{3}}{\frac{10}{9}} = \frac{2}{3} \times \frac{9}{10} = \frac{6}{10} = \frac{3}{5} \][/tex]
[tex]\[ \cos 2\phi = \frac{1 - \tan^2 \phi}{1 + \tan^2 \phi} = \frac{1 - \left(\frac{1}{3}\right)^2}{1 + \left(\frac{1}{3}\right)^2} = \frac{1 - \frac{1}{9}}{1 + \frac{1}{9}} = \frac{\frac{8}{9}}{\frac{10}{9}} = \frac{8}{10} = \frac{4}{5} \][/tex]
Now, calculate [tex]\(\sin 4\phi\)[/tex]:
[tex]\[ \sin 4\phi = 2 \sin 2\phi \cos 2\phi = 2 \left(\frac{3}{5}\right) \left(\frac{4}{5}\right) = 2 \times \frac{12}{25} = \frac{24}{25} \][/tex]
Thus,
[tex]\[ \sin 4\phi = 0.96 \][/tex]
4. Conclusion:
We have found that:
[tex]\[ \cos 2\theta = 0.96 \quad \text{and} \quad \sin 4\phi = 0.96 \][/tex]
Therefore,
[tex]\[ \cos 2\theta = \sin 4\phi \][/tex]
Hence, it is proven that [tex]\(\cos 2\theta = \sin 4\phi\)[/tex].
### Step-by-Step Solution:
1. Represent [tex]\(\theta\)[/tex] and [tex]\(\phi\)[/tex] using arctangent:
Since [tex]\(\tan \theta = \frac{1}{7}\)[/tex], we have:
[tex]\[ \theta = \tan^{-1}\left(\frac{1}{7}\right) \][/tex]
Similarly, since [tex]\(\tan \phi = \frac{1}{3}\)[/tex], we have:
[tex]\[ \phi = \tan^{-1}\left(\frac{1}{3}\right) \][/tex]
2. Double-angle formula for cosine:
For [tex]\(\cos 2\theta\)[/tex], we use the double-angle identity for cosine in terms of tangent:
[tex]\[ \cos 2\theta = \frac{1 - \tan^2 \theta}{1 + \tan^2 \theta} \][/tex]
Substituting [tex]\(\tan \theta = \frac{1}{7}\)[/tex]:
[tex]\[ \cos 2\theta = \frac{1 - \left(\frac{1}{7}\right)^2}{1 + \left(\frac{1}{7}\right)^2} = \frac{1 - \frac{1}{49}}{1 + \frac{1}{49}} = \frac{\frac{48}{49}}{\frac{50}{49}} = \frac{48}{50} = \frac{24}{25} \][/tex]
Thus,
[tex]\[ \cos 2\theta = 0.96 \][/tex]
3. Double-angle formula for sine:
To find [tex]\(\sin 4\phi\)[/tex], use the identity:
[tex]\[ \sin 4\phi = 2 \sin 2\phi \cos 2\phi \][/tex]
First, find [tex]\(\sin 2\phi\)[/tex] and [tex]\(\cos 2\phi\)[/tex] using the double-angle formulas for sine and cosine:
[tex]\[ \sin 2\phi = \frac{2 \tan \phi}{1 + \tan^2 \phi} \][/tex]
Substituting [tex]\(\tan \phi = \frac{1}{3}\)[/tex]:
[tex]\[ \sin 2\phi = \frac{2 \left(\frac{1}{3}\right)}{1 + \left(\frac{1}{3}\right)^2} = \frac{\frac{2}{3}}{1 + \frac{1}{9}} = \frac{\frac{2}{3}}{\frac{10}{9}} = \frac{2}{3} \times \frac{9}{10} = \frac{6}{10} = \frac{3}{5} \][/tex]
[tex]\[ \cos 2\phi = \frac{1 - \tan^2 \phi}{1 + \tan^2 \phi} = \frac{1 - \left(\frac{1}{3}\right)^2}{1 + \left(\frac{1}{3}\right)^2} = \frac{1 - \frac{1}{9}}{1 + \frac{1}{9}} = \frac{\frac{8}{9}}{\frac{10}{9}} = \frac{8}{10} = \frac{4}{5} \][/tex]
Now, calculate [tex]\(\sin 4\phi\)[/tex]:
[tex]\[ \sin 4\phi = 2 \sin 2\phi \cos 2\phi = 2 \left(\frac{3}{5}\right) \left(\frac{4}{5}\right) = 2 \times \frac{12}{25} = \frac{24}{25} \][/tex]
Thus,
[tex]\[ \sin 4\phi = 0.96 \][/tex]
4. Conclusion:
We have found that:
[tex]\[ \cos 2\theta = 0.96 \quad \text{and} \quad \sin 4\phi = 0.96 \][/tex]
Therefore,
[tex]\[ \cos 2\theta = \sin 4\phi \][/tex]
Hence, it is proven that [tex]\(\cos 2\theta = \sin 4\phi\)[/tex].
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.